Pengaruh Employability Skill terhadap Kesiapan Kerja yang Dimoderasi oleh Dukungan Sosial pada Mahasiswa Universitas Negeri Padang - Arham, Ulil; Nio, Suci Rahma (Lembaga Yasin AlSys, 2025)
This study aims to analyze the influence of employability skills on job readiness, with social support as a moderating variable among students at Universitas Negeri Padang. A quantitative method was employed using a survey approach and purposive sampling technique, resulting in a sample of 409 students. Data were analyzed using Moderated Regression Analysis (MRA) to assess both the direct effect of employability skills on job readiness and the moderating role of social support. The results show that employability skills have a positive impact on job readiness. Social support significantly moderates this relationship with a negative direction (buffering effect). Furthermore, employability skills contributed 59.4% to students’ job readiness, while the inclusion of social support as a moderating variable strengthened the interaction effect to 63.5%. These findings underscore the importance of mastering employability skills to enhance students' job readiness, with social support playing a significant role in shaping the dynamic between the two.